2019
DOI: 10.1007/s10479-019-03338-4
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting benchmarks of long-term stock returns via machine learning

Abstract: Recent advances in pension product development seem to favour alternatives to the risk free asset often used in the financial theory as a performance standard for measuring the value generated by an investment or a reference point for determining the value of a financial instrument. To this end, in this paper, we apply the simplest machine learning technique, namely, a fully nonparametric smoother with the covariates and the smoothing parameter chosen by cross-validation to forecast stock returns in excess of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 35 publications
3
42
0
Order By: Relevance
“…Kyriakou et al studied the application of machine learning in stock return research [63]. Moat et al found that the data on the change of page views of Wikipedia's financial pages contained the early signs of the stock market trend, so the online data were useful in the information collection stage before the decision [64]. 1 represents the cited times in the its cluster we selected, not the real cited times.…”
Section: Big Data Financementioning
confidence: 99%
“…Kyriakou et al studied the application of machine learning in stock return research [63]. Moat et al found that the data on the change of page views of Wikipedia's financial pages contained the early signs of the stock market trend, so the online data were useful in the information collection stage before the decision [64]. 1 represents the cited times in the its cluster we selected, not the real cited times.…”
Section: Big Data Financementioning
confidence: 99%
“…Its goal is to develop non-biological systems to perform tasks that usually require human intelligence. Artificial intelligence and big data technology have shaped various aspects of business and management (Grover et al 2020;Kyriakou et al 2019). For example, Akter et al 2020introduced a Netflix's recommendation system, which first mines user data and then adopts different models to determine the most suitable recommendation system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The latter is until today an open question; presently, cross-validation-type methods are the most popular ones. For kernel based methods, see Heidenreich et al (2013) and Köhler et al (2014) for a review or Nielsen and Sperlich (2003) in the context of forecasting in finance.…”
Section: Preliminary Considerations and General Ideasmentioning
confidence: 99%
“…Following Nielsen and Sperlich (2003), Kyriakou et al (2019), and Mammen et al (2019), you could use local linear regression in Step 1 for both functions, combined with the validated R 2 for the bandwidth choice. Obviously, any method known as ML, including LASSO variable selection, can be applied in this step.…”
Section: Combining the Prior With Nonparametric Estimationmentioning
confidence: 99%
See 1 more Smart Citation